2019
DOI: 10.1192/bjp.2019.110
|View full text |Cite
|
Sign up to set email alerts
|

Urbanicity and risk of first-episode psychosis: incidence study in Brazil

Abstract: We estimated the incidence of first-episode psychosis over a 3-year period in a Brazilian catchment area comprising the region's main city, Ribeirão Preto (1 425 306 persons-years at risk), and 25 other municipalities with a total of 1 646 556 persons-years at risk. The incidence rates were estimated and adjusted by gender and age, using the direct standardisation method to the world population as reference. The incidence of psychosis was higher in the younger groups, men, and among Black and minority ethnic B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 13 publications
0
28
1
9
Order By: Relevance
“…Subjects. This case-sibling-control study is part of an incidence study of mental disorders with psychotic symptoms named STREAM (Schizophrenia and Other Psychoses Translational Research: Environment and Molecular Biology) conducted in the Ribeirão Preto catchment area, Brazil, between 1st of April 2012 and 31st of March 2015 29 . This Brazilian incidence study is part of the consortium European Network of National Schizophrenia Networks Studying Gene-Environment Interactions (EU-GEI) 30,31 .…”
Section: Methodsmentioning
confidence: 99%
“…Subjects. This case-sibling-control study is part of an incidence study of mental disorders with psychotic symptoms named STREAM (Schizophrenia and Other Psychoses Translational Research: Environment and Molecular Biology) conducted in the Ribeirão Preto catchment area, Brazil, between 1st of April 2012 and 31st of March 2015 29 . This Brazilian incidence study is part of the consortium European Network of National Schizophrenia Networks Studying Gene-Environment Interactions (EU-GEI) 30,31 .…”
Section: Methodsmentioning
confidence: 99%
“…This case-sibling-control study is part of the epidemiological investigation named STREAM (Schizophrenia and Other Psychoses Translational Research: Environment and Molecular Biology) conducted in Ribeirão Preto catchment area (comprised of 26 counties with around 1.3 million inhabitants, located in the São Paulo state, Brazil) between April 2012 and March 2015 (Del-Ben et. al., accepted). The STREAM study is part of the international multicentre consortium EU-GEI (European Network of National Schizophrenia Networks Studying Gene-Environment Interactions; ), an incidence and case-sibling-control study investigating biological and environmental interactions in psychosis (Jongsma et al ., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…These findings are in line with those from a previous study performed in the same areas, with a larger number of participants, and with MD identified using a screening instrument. 15 …”
Section: Discussionmentioning
confidence: 99%
“…This article refers to Phase 2 of a large cross-sectional study. Phase 1, described in a previous publication, 15 involved 1,545 subjects randomly selected on the basis of a household geographical information system covering the three areas (FHS, FHS+SC, and TC). 16 A random sample – involving 50% of Phase 1 participants – was contacted and invited to participate in Phase 2.…”
Section: Methodsmentioning
confidence: 99%